용액 공정을 접목한 전기화학 증착 기법을 활용한 금 나노 구조체 제작 - 김지희; 김동현; 강미정; Jihee Kim; Donghyeon Kim; Mijeong Kang (전기화학회지, 2024)
Nanomaterial electrodes are used to improve the analytical performances of electrochemical measurements in biological and chemical field. Frequently used methods for fabricating metal nanostructures are solution processing and electrodeposition. In the solution process, it is possible to control the characteristics (e.g., direction) of metal growth by using capping agents, thereby fabricating nanoparticles of specific structures. In the electrodeposition, the electrode surface and the deposited metal atoms are in direct contact. Each process has its own limitation as well, and many studies are conducted to overcome such limitation. In this paper, we report an integration of the two fabrication methods and the characteristics, such as structural and electrochemical properties, of the fabricated electrodes. Lastly, we discuss the possibility of using the fabricated nanostructured electrode as a sensor. 나노 소재 전극은 바이오/화학 분야에서 분석 성능을 향상시키기 위한 핵심 요인으로 활용되고 있다. 금속 나노 소재를 제작하는 방법으로는 크게 용액 공정과 전기증착 공정이 있다. 용액 공정에서 capping agent를 사용하면 금속 원자의 결합 방향을 통제할 수 있어 특이적 구조의 나노 입자를 얻을 수 있고, 전기증착 공정을 이용하면 전극 표면과 금속 원자 사이의 직접적인 결합이 일어나서 높은 결합력을 기대할 수 있다. 이 공정들은 각각의 장점을 가지고 있으나, 문제점 또한 있어 이를 해결하기 위해 많은 연구가 진행되고 있다. 이 논문에서는 전극용 금속 나노 소재를 제작하는 두 기법의 융합, 그로부터 확보한 나노 구조 전극 및 그것의 전기화학적 특성을 살펴보고, 그러한 나노 구조 전극의 센서로서의 활용 가능성에 대해 이야기하고자 한다.